Treatment for Paget's disease: surgical approaches - E. Yu. Fetisova; A. D. Zikiryakhodzhaev; N. N. Volchenko (ABV-press, 2015)
Breast cancer (BC) ranks first in the pattern of female malignancies (20.7 %) and remains the top cancer among women. Paget's disease (PD) is a rare BC form that occurs in the orifice of the lactiferous tubes and that is characterized by involvement of the nipple, large ducts, often to form a lump in the breast; this rare abnormality is encountered in 0.5-5 % of all BC cases. PD has a number of peculiarities. According to different authors, PD is attended with invasive or noninvasive BC in most cases (90-98 %). The involvement is commonly multifocal. PD has a very high risk for a lump (100 and 96 % for palpable and nonpalpable breast tumors, respectively). Almost 50 % of these patients have palpable breast lumps. Despite the fact that the course of PD has its peculiarities because of the rarity of this abnormality, the approaches to its treatment are not different from those in other histopathological types of BC. As for the surgical treatment of PD, until the present time there have been many unsolved problems that remain a matter of debate. The surgical treatment of PD does not differ from the treatment of BC and is primarily determined by disease stage and tumor subtype. The volume of operations for PD varies: from Madden's radical mastectomy to lumpectomy and sentinel lymph node biopsy. It should be kept in mind that besides nipple-areole complex involvement, invasive or noninvasive BC is often detected in PD. Organ-sparing surgery for PD is mainly a method of rehabilitation for patients. Whether organsparing surgery can be performed is also determined by breast size. Oncoplaplastic resections may be carried out for PD. If the patient wishes to preserve her breast, the range of both single-stage and delayed reconstructive operations is wide. The assessment of the biological features of a tumor and the more differentiated approach to therapy in this cohort of patents might improve considerable survival rates; the determination of indications for organ-sparing treatment is to improve quality of life in patients and their rehabilitation.